THE INTERSECTION OF ISLAMIC EPISTEMOLOGY AND HIGHER EDUCATION CONTEXT: ANALYZING THE ROLES AND CHALLENGES IN SHAPING THE ISLAMIC IDENTITY OF STUDENTS - Nurbiah Pohan; Firmansyah; Maulana Arafat Lubis; Nashran Azizan; Muhammadong (International Journal of Teaching and Learning, 2024)
This study delves into the intricate interplay between Islamic epistemology and higher education, examining their roles and challenges in shaping the Islamic identity of students. Grounded in a qualitative approach, the research draws insights from reputable publications to provide a nuanced comprehension of this intersection. Participants from diverse higher education settings, including Islamic nations, contribute to exploring Islamic values' impact on identity formation. The roles of Islamic epistemology in shaping identity emerge as a significant theme, highlighting its versatile influence across academic disciplines. Participants emphasize a profound connection between Islamic values, rooted in the Quran and the teachings of Prophet Muhammad, and their engagement with knowledge. The integration of these values extends beyond academic pursuits, fostering a holistic understanding of the world and instilling a sense of purpose and ethical responsibility among students. However, challenges within this intersection are evident, with tensions arising from diverse perspectives in academic discourse. The limited representation of Islamic perspectives in curricula poses a universal challenge, impacting students' ability to integrate their Islamic identity into their educational journey fully. The study also explores institutional dynamics, emphasizing the pivotal role of supportive environments in higher education institutions  within  Islamic  nations.  In  conclusion,  the  research  offers comprehensive insights into the universal roles and challenges within the intersection of Islamic epistemology and higher education, calling for global attention to create inclusive educational environments that respect diverse religious identities, including the Islamic identity of students.